القناع في شعر البياتي ونثره - يسير خالد (Latakia University Journal - Arts and Humanities Sciences Series, 2019)
يتناول البحث استخدام البياتي لتقنية القناع ، في شعره ، وحديثه عنه نظرياً في نثره ، وقد كان رائداً في ذلك ، ويمكن رد مصادر القناع عنده إلى : قناع الشخصيات المعاصرة ، وقناع الشخصيات التراثية ، وقناع الأمكنة .كما تجلّت أشكال القناع في شعره في ثلاثة نماذج ، هي : قناع النص ، وقناع الديوان ، وهو نادر ، وقناع النتاج الكامل الذي يتكرر في نتاج الشاعر على مرحلة زمنية طويلة . وقد وظَّف البياتي القناع للتعبير عن المحن الاجتماعية والكونية بأسلوب مباشر ، تغلب عليه الغنائية والذاتية ، وتراوح موقفه بين التفاؤل والتشاؤم ، ثم تتطور ثقافته ، وتتعمق ، وتتنوع أدواته التعبيرية ، فيصبح توظيف القناع عنده أكثر عمقاً في النفس البشرية ، وأكثر غوصاً في تاريخها ، فراحت الأقنعة تكشف مفارقات الحياة وضراوتها ، وتصوّر كفاح الروح من أجل تخليص العالم من شروره ، ومن طغاته . لقد اعتمدت خطوات البحث قراءة النصوص النثرية والشعرية أولاً ، ثم النظرة التاريخية التطورية ثانياً ، وخلصت إلى خاتمة ، تناولت هنات الشاعر في استخدامه للقناع . This paper deals with AL-Bayaty’s use of the persona technique in poetry and prose, In this respect, He was a pioneer, His employment of personas can be attributed to varied sources : modern, classical and geographical, In his poetry, three different types of personas recurred : textual, anthological ( which are rare and total, recurring throughout a poet’s literary out put over a time duration . AL-Bayaty has made use of persona in order to reflect social and universal dilemmas in a direct style tinged with lyricism and subjectivity . this attitude as a poet oscillates between optimism and pessimism. With the development and maturation of his culture, and the variation of his poetic techniques, his employment of persona has become more probing of human psyche and its history . The personas have, consequently, uncovered the discipancies and harshness of human life and depicted the spiritual struggle to get rid the world of evils and tyrants . This research relied, first on exploring prose and verse texts, then, used an historical evolutionary perspective, and reaches the conclusion that highlighted the poet’s mishaps in the employment of persona .